The impact of expanded health system reform on governmental contributions and individual copayments in the new Chinese rural cooperative medical system - Dong, Hengjin; Duan, Shengnan; Bogg, Lennart; Wu, Yuan; You, Hua; Chen, Jianhua; Ye, Xujun; Seccombe, Karen; Yu, Hai (The international journal of health planning and management, 2016)
In 2002, the Chinese central government created a new rural cooperative medical system (NCMS), ensuring that both central and local governments partner with rural residents to reduce their copayments, thus making healthcare more affordable. Yet, significant gaps in health status and healthcare utilization persisted between urban and rural communities. Therefore, in 2009, healthcare reform was expanded, with (i) increased government financing and (ii) sharply reduced individual copayments for outpatient and inpatient care. Analyzing data from China's Ministry of Health, the Rural Cooperative Information Network, and Statistical Yearbooks, our findings suggest that healthcare reform has reached its preliminary objectives—government financing has grown significantly in most rural provinces, especially those in poorer western and central China, and copayments in most rural provinces have been reduced. Significant intraprovincial inequality of support remains. The central government contributes more money for poor provinces than for rich ones; however, NCMS schemes operate at the county level, which vary significantly in their level of economic development and per capital gross domestic products (GDP) within a province. Data reveal that the compensation ratios for both outpatient and inpatient care are not adjusted to compensate for a rural county's level of economic development or per capita GDP. Consequently, a greater financial burden for healthcare persists among persons in the poorest rural regions. A recommendation for next step in healthcare reform is to pool resources at prefectural/municipal level and also adjust central government contributions according to the GDP level at prefectural/municipal level. Copyright © 2014 John Wiley & Sons, Ltd.
Published online 22 May 2014
Gesehen am 11.05.2020